Auditory Meaning-Making in Multimodal Documentary Discourse: Functions, Features, and Synergies - Wenhan Pan (Yayasan Visi Intan Permata, 2025)
This study explores how sound helps shape cultural meaning in the English-language documentary Festive China. While most multimodal research has focused on images and text, sound has received less attention. This paper aims to fill that gap by examining the use of narration, background music, and ambient sound in the film. The analysis focuses on five key features of sound: loudness, pitch, rhythm, timbre, and brightness. The study uses a qualitative method based on Systemic Functional Linguistics and multimodal discourse analysis. It looks at how sound works with visuals and language to build meaning in three ways: what is shown, how the audience is engaged, and how the content is organized. The results show that narration explains ideas and builds emotional tone. Background music creates mood and supports the story’s rhythm. Ambient sounds add realism and connect viewers to the setting. These elements often work together to support themes like celebration, memory, and tradition. The sound design also reflects cultural values such as balance and harmony. By focusing on audio modality, this study adds to current multimodal research and shows the importance of sound in meaning-making. It also offers insights for educators who want to help students better understand how documentaries use sound to share cultural ideas.